PEMANFAATAN SAMPAH PLASTIK MENJADI ToSAPlas (TONG SAMPAH ASLI PLASTIK) UNTUK MENGURANGI RESIKO DARI SAMPAH PLASTIK - Neneng Fitrya; Sri Fitria Retnawaty; Noni Febriani; Yulia Fitri; Shabri Putra Wirman; Delovita Ginting (Jurnal Pengabdian UntukMu NegeRI, 2019)
Community service aims to provide training to the entire academic community of IT Fadillah High School, Pekanbaru, about the use of plastic waste into useful and feasible items. This aims to minimize the risk of plastic waste because plastic has properties that are non-biodegradable and take a long time to be decomposed naturally on the ground. The items to be made are handicrafts in the form of plastic trash cans (ToSAPlas). The implementation of the activity uses lecture, demonstration and discussion methods. The lecture was filled with training materials on making ToSAPlas covering preparation of raw materials for supporting tools and materials, plastic cleaning, plastic cutting, weaving, finishing. The demonstration method was carried out by the service team by dividing the participants into 6 groups. Each group was accompanied by one member of the service team and practiced directly how the process of making ToSAPlas. The target of this service program is to increase lecturers' awareness of the environment and society, while for the partners this activity is a forum for discussion in developing creative ideas in the field of recycling plastic waste and making business products that can be offered in the market. Keywords: Waste, Plastics, ToSAPlas